ANALISIS PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA KANTOR KEMENTRIAN AGAMA KOTA SINGKAWANG - Sudarso, Erik (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
This study was conducted to determine how much influence Training and Career Development has on Employee Performance at the Ministry of Religious Affairs Office of Singkawang City. The research method used is quantitative research with data collection techniques using questionnaires and using probability sampling techniques alongside simple random sampling in taking samples. The data used are profile data from the Ministry of Religious Affairs Office of Singkawang City, questionnaire data, primary processed data, and processed data from SPSS Version 25. Based on the results of the T test or partial test, it shows that the significant value of Training and Career Development has a positive effect on Employee Performance. The F test shows that the significant value of 0.000 is smaller than 0.05, so Training and Career Development simultaneously have an effect on Employee Performance. Based on the results of the Determination Test (R2), the R2 value is 0.361 or 36.1 percent. The suggestion submitted by the author, namely the Office of the Ministry of Religion of Singkawang City should be able to use the results of the research on the influence of Training and Career Development can be used as information in viewing employee performance which can be used to help improve Training and develop employee careers so that it can increase motivation in working and improve employee performance.